5x^2 + 8x - 2 = 0
5x^2 + 8x = 2
x^2 + (8/5)x = (2/5)
x^2 + (8/5)x + (16/25) = (26/25)
(x + (4/5))^2 = (26/25)
x + (4/5) = sqrt(26/25)
x + (4/5) = ±(1/5)sqrt(26)
x = (-4/5) ± (1/5)sqrt(26)
or
x = (1/5)(-4 ± sqrt(26))
--------------------------------------------
15 - 6x - 2x^2 = 0
-2x^2 - 6x + 15 = 0
-(2x^2 + 6x - 15) = 0
2x^2 + 6x - 15 = 0
2x^2 + 6x = 15
x^2 + 3x = (15/2)
x^2 + 3x + (9/4) = (39/4)
(x + (3/2))^2 = (39/4)
x + (3/2) = sqrt(39/4)
x + (3/2) = (1/2)sqrt(39)
x = (-3/2) ± (1/2)sqrt(39)
or
x = (1/2)(-3 ± sqrt(39))
2006-09-15 12:46:08
·
answer #1
·
answered by Sherman81 6
·
1⤊
0⤋
OK! I will show you the path...
Note: (x+a)^2 = x^2 +2ax + a^2 is the complete square
When we find a non-complete square like x^2 + 2ax .... we must follow the steps:
1) The coeficient of x^2 must be 1. If it is not you divide the equation so that it change to 1
2)Take apart the coeficient of x and divide it by 2. So you get the value of a.
3) Add and subtract a^2 to the equation
4) The three first terms are the complete square (x+a)^2 and you put the other terms to the other side, adding them... it will be a number b.
5) Now you have (x+a)^2 = b and the solutions are:
x+a = sqrt(b) or x+a = -sqrt(b) and finally you got the solutions: x= -a+sqrt(b) or x= -a -sqrt(b)
Let´s do the first for you:
5x^2 + 8x - 2 = 0
1) divide all by 5 x^2 + (8/5)x - 2/5 = 0
2) take the coeficiente 8/5 apart and divide by 2... a=4/5
3) add and subtract 16/25 to the equation
x^2 + (8/5)x + 16/25 - 16/25 -2/5 = 0
4) the first 3 terms are the complete square
(x - 4/5)^2 = 16/25+2/5 add the number in side 2
5) (x-4/5)^2 = 36/25 and x-4/5 = 6/5 or x-4/5 = -6/5
and finally x= 4/5 +6/5 = 2 or x = 4/5 -6/5 = -2/5
Now you work
2006-09-15 08:42:40
·
answer #2
·
answered by vahucel 6
·
0⤊
0⤋
1) 5x^2 + 8x = 2
x^2 + 8/5 x = 2/5
add (8/10)^2 to each side
(x + 8/10 )^2 = 2/5 + (8/10)^2
solution x+ 8/10 = + or - sqrt(2/5 + (8/10)^2)
solve x now and get the answers
2) same apllies to the other equation
2006-09-15 08:44:14
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
On first one, divide each side by 5, giving you x^2+(8/5)x-(2/5)=0.
Now, to find out what constant value has to be on left side, divide
8/5 by 2, and square it, giving you (8/10)^2 = 64/100.
Now, that means you have to add (64/100)+(2/5) to each side.
So, (64/100)+(2/5) = (64/100)+(40/100) = 104/100.
So, that gives you x^2+(8/5)x+(64/100) = 104/100, or
(x+(8/10))^2 = 104/100.
So, can you do the next one?
2006-09-15 08:45:42
·
answer #4
·
answered by yljacktt 5
·
0⤊
0⤋
2x^2-6x+15
(2x^2+__+15)-6x
Does that help?
2006-09-15 08:24:52
·
answer #5
·
answered by ice_purple969 4
·
0⤊
0⤋
It is explained very well here
2006-09-15 08:21:24
·
answer #6
·
answered by Philip W 7
·
0⤊
0⤋
Cool....contact me.
2006-09-15 08:19:40
·
answer #7
·
answered by Anonymous
·
0⤊
1⤋